Performance and Obstacles of SMEs: An Empirical Evidence from BRICS Countries - Noshad, Madiha; Amjad, Mariam; Shafiq, Muhammad Nouman; Gillani, Seemab (iRASD Journal of Economics, 2019)
This study empirically examines the performance and obstacles of SMEs in BRICS economies. For empirical evaluation, Ordinary Least Square technique has applied by taking the time period between “2000-2017”. Performance has taken as dependent variable and obstacles; firm characteristics and global factor have taken as explanatory variables. Estimated results show that ownership and size have a positive impact on SMEs growth and performance. Age has a negative and significant impact on the performance and growth of SMEs. Technology has a positive and significant impact on the performance of SMEs. Obstacles i.e. courts, crime, access to finance, practices of competitors and electricity has a negative and significant impact on the performance of SMEs. Access to land, infrastructure and workforce has a positive and significant impact on SMEs performance. It becomes very important for the policymakers or investigators to pay attention towards making SMEs more competent, capable and productive in order to attain the goal of sustainable development and progress.